2022
DOI: 10.3390/ijms23031026
|View full text |Cite
|
Sign up to set email alerts
|

Hemosiderin Accumulation in Liver Decreases Iron Availability in Tachycardia-Induced Porcine Congestive Heart Failure Model

Abstract: Despite advances in the management of iron deficiency in heart failure (HF), the mechanisms underlying the effects of treatment remain to be established. Iron distribution and metabolism in HF pathogenesis need to be clarified. We used a porcine tachycardia-induced cardiomyopathy model to find out how HF development influences hepatic and myocardial iron storing, focusing on ferritin, the main iron storage protein. We found that cumulative liver congestion (due to the decrease of heart function) overwhelms its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…Thus, our data showed considerable differences in the expression of genes involved in iron metabolism in the heart and the liver of rats. In agreement, a recent study by Kasztura et al [ 63 ] has shown that the mechanisms of iron uptake, storage and clearance differ between the liver and heart in the porcine model of heart failure progression.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, our data showed considerable differences in the expression of genes involved in iron metabolism in the heart and the liver of rats. In agreement, a recent study by Kasztura et al [ 63 ] has shown that the mechanisms of iron uptake, storage and clearance differ between the liver and heart in the porcine model of heart failure progression.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, the iron balance in various human disease stages and safe iron supplementation in different clinical conditions are being studied with increasing attention. It has been observed that in physiological conditions, iron is not excreted from the body, and any iron excess is stored in safe cell deposits in the form of ferritin, distributed mainly in the liver macrophages, spleen, and other organs and cells [ 7 ]. In the presented study, Western blotting showed the presence of good quality bands for ferritin and soluble transferrin receptor, which did not differ between the studied groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the prognosis and survival of HF patients with ID (with or without anemia) are worse compared to HF patients without ID, the European Society of Cardiology (ESC) recommends supplementing iron intravenously, e.g., with ferric carboxymaltose, in HF patients with ID [ 13 , 18 ]. Iron deficiency has been reported in animals (pigs and rodents) with experimentally induced HF [ 7 , 24 ]. However, only a few studies on iron management in HF dogs are available [ 22 , 25 ], despite HF being a common disease of older and small breed dogs, especially Cavalier King Charles Spaniel (CKCS), dachshund, miniature poodle, Maltese, Chihuahua, Pomeranian, or Yorkshire terriers [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 82 FTH1 exhibits iron oxidase activity, converting excess Fe 2+ to Fe 3+ , while FTL allows for Fe 3+ storage. 83 Fe 2+ is mainly excreted from the cell membrane by the solute carrier family 40 member 1 (SLC40A1) or can be expelled as Ferritin via exosomes. 84 The protein prominin 2 promotes the formation of polyvesicles and exosomes, facilitating iron excretion from cells and maintaining the dynamic equilibrium of intracellular iron levels.…”
Section: Regulation Of Intracellular Biochemical Processes On Ferropt...mentioning
confidence: 99%